Intergenerational Persistence of Health: Evidence from India - Santosh Kumar; Bernard Nahlen (Institute of Labor Economics (IZA), 2023)
Using nationally representative data, we estimate intergenerational persistence in health in India. Results from the instrumental variable method show that children of anemic mothers are more likely to be anemic, with an intergenerational health correlation of 0.26. Results are robust to the inclusion of confounding factors including the mother's height. We find that the correlation between mothers' anemic status and children's anemic status differs by wealth quintile, indicating that economic status may play a role in the persistence of poor health across generations in developing countries.
Keywords: I10; I14; O15; 330; intergenerational mobility; health; anemia; India